PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - Lokaputra Michael; Anugerah Rita; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Disclosure of risk management is a disclosure of the risks that have been managed by the company or disclosure of how the company will control risks related to the future. The purpose of this study was to determine the effect of corporate governance such as managerial ownership, institutional ownership, independent commissioners, audit committees and risk management committees on risk management disclosure. The population of this study are non-bank financial services companies listed on the Indonesian stock exchange in 2016-2019. The sample selection method was carried out by purposive sampling, namely the method of selecting samples with certain criteria. The sample according to the criteria is 31 companies with an observation period of 4 years so that the research sample is 124. The results of the study indicate that managerial ownership has an effect on risk management disclosure. Institutional ownership factors affect the disclosure of risk management. The independent commissioner factor has no significant effect on risk management disclosure. The audit committee factor has an effect on risk management disclosure. The risk management committee factor has an effect on risk management disclosure.Keywords : Disclosure of Risk Management, Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee, and Risk Management Committee.